Climate change and Epichloë coenophiala association modify belowground fungal symbioses of tall fescue host. (February 2018) - Slaughter, Lindsey C.; Nelson, Jim A.; Carlisle, Elizabeth; Bourguignon, Marie; Dinkins, Randy D.; Phillips, Timothy D.; McCulley, Rebecca L.
Abstract: Human alteration of symbiont genetics among aboveground endophytic Epichloë coenophiala strains within tall fescue ( Schedonorus arundinaceus ) has led to widespread deployment of novel grass-endophyte combinations, yet little is known about their ecological consequences. In this study, clone pairs (endophyte-infected, endophyte-free) of two tall fescue genotypes received factorial combinations of increased temperature (+3 °C) and precipitation (+30% long-term annual mean) for 2 yr. We measured root arbuscular mycorrhizal fungi (AMF), dark septate endophyte (DSE) colonization, and soil AMF extraradical hyphae (ERH) length. We hypothesized that genetically distinct grass- E. coenophiala associations would differentially affect belowground fungi, and that these relationships would be climate-sensitive. Tall fescue genotype, endophyte presence, and climate treatment interactions affected AMF arbuscules, vesicles, and ERH. DSE decreased with E. coenophiala presence but increased with warming. Genetically distinct tall fescue- E. coenophiala associations may have divergent long-term impacts on other host-symbiont interactions, potentially impacting ecosystem function and response to climate change. Highlights: Genetic E+, E− tall fescue clones received field warming and precipitation addition. Grass genotype, E+/E−, and climate treatments affected root and soil AMF structures. DSE decreased with E. coenophiala presence but increased with warming. Host-symbiont genetics influence AMF, can be modified by climate change. E. coenophiala -grass combinations alter root/soil fungi and climate change response.